WORKSHOP COPYWRITING DAN SEO UNTUK MENINGKATKAN PEMASARAN DIGITAL UMKM PURI AREN CAIR - Harahap, Muharrina; Anggreini, Heny; Jakaria, Jakaria; Munthe, Abdillah Menri (Jurnal Pepadu, 2025)
Modernization and the development of digital technologies provide great opportunities for UMKM to expand their market through e-commerce. However, UMKM Puri Aren Cair still faces obstacles in its digital marketing strategy so that online sales are not optimal despite having a potential flagship product in the national and international markets. The purpose of this devotional activity is to increase the digital literacy and marketing capacity of partners through training in copywriting, SEO, as well as the professional use of e-commerce. The method of the activity was implemented on a participatory basis in July 2025 involving ten employees of UMKM Puri Aren Cair. The stages of the activities included socialization, training, application of technology, mentoring, evaluation, and sustainability of the program. Participants attended a two-day workshop focused on copywriting strategies, SEO, and managing online stores in the marketplace. The results of the activity show a significant improvement in the digital literacy of the participants, the skills of managing online stores, as well as the ability to optimize promotional content based on digital marketing strategies. Implementing digital strategies through e-commerce has the potential to expand market reach, strengthen branding, and increase sales. In conclusion, this dedicated activity is successful in addressing the main problem of the partners, namely the limitations of the digital marketing strategy, by providing practical solutions that support the improvement of the competitiveness of UMKM in the era of industry 4.0.